Review: Penggunaan Off-Label Obat Golongan Antagonis Reseptor Histamin 2 - Indah Sari; Ellin Febrina (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Histamine 2 (H2) receptor antagonist drugs have been widely used for a wide range of indications, including for use as off-label drugs. Even though it can potentially increase the risk of adverse drug reactions, under certain conditions, using off-label drugs is the only option for medical personnel. This review aims to provide an overview of the widespread off-label use of H2 receptor antagonists, including ranitidine, cimetidine, famotidine, and nizatidine. The results of this review are expected to be used as evaluation material by the government, drug manufacturers, and health practitioners. The method used in this review is a study of literature obtained through several services, such as PubMed®, ScienceDirect®, and Google Scholar. The results of this review show that using off-label H2 receptor antagonist drugs is a curative and preventive effort to overcome several diseases, namely off-label in the categories of patient age, dosage, and indications.